Endophytic Fungi of Calea pinnatifida (Asteraceae): Dereplication of Crude Extracts, Antimicrobial Properties, and Identification of New Tetronic Acid Derivative Produced by Hypomontagnella barbarensis - Bianca Barna; Lhaís Araújo Caldas; Jackson Monteiro; Augusto Leonardo dos Santos; Renata Castiglioni Pascon; Marcelo Afonso Vallim; Marcelo José Pena Ferreira; Sarah Santos Gonçalves; Glaucia Queiroz dos Santos; Anderson Messias Rodrigues; Jamile Ambrósio de Carvalho; Suzan Pantaroto de Vasconcellos; et al. (Journal of Fungi)
Endophytic fungi are increasingly being recognized for their diverse metabolites that may exhibit antimicrobial properties. In our study, we isolated seven endophytic fungal strains from Calea pinnatifida, which were identified as Hypomontagnella barbarensis, Neopestalotiopsis clavispora, Nigrospora sacchari-officinarum, Annulohypoxylon moriforme, Colletotrichum siamense, and Colletotrichum karstii (with two isolates from the same species). Furthermore, the antimicrobial activity of the extracts was assessed, revealing that the extract from Hypomontagnella barbarensis demonstrated activity against Staphylococcus aureus. Further investigation of secondary metabolites, employing UHPLC-HR-ESI-MS/MS in combination with molecular networking, facilitated annotation of the nine compounds. Of these, five were identified based on matches with the GNPS spectral library, and four were predicted based on the molecular network. Notably, from the extract of Hypomontagnella barbarensis, two pairs of diastereoisomeric acyl-tetronic acid derivatives were isolated and characterized using MS and NMR spectroscopy. This study highlights the potential of endophytic fungi as a valuable source of novel antimicrobial agents.